High Flow in the Storm. Early Administration of High-Flow Nasal Cannula in Patients with Severe Acute Hypoxic Respiratory Failure Due to Clinically Suspected COVID-19 - López Escobar, Alejandro; Jimeno, Sara; Gómez, Máximo; Sol Ventura, Paula; Calle, Ángeles; Núñez, Elena; Castellano, José María (My University, 2024)
Background: The worldwide COVID-19 pandemic has created a shortage of ICU beds and ventilators. The objective was to assess whether administration of high-flow nasal cannula (HFNC) in patients with acute hypoxic respiratory failure due to COVID-19 averted mechanical ventilation (MV). Methods: Prospective observational study performed at Hospital Universitario HM Puerta del Sur (Madrid). The protocol included early administration of HFNC in clinically suspected COVID-19 patients with progressive desaturation. Results: Twenty patients were started on respiratory support with HFNC. Hospital admission took place after a median of 7 days since symptom onset and clinical deterioration was apparent at 9 days after symptom onset. Anti-inflammatory treatment with methylprednisolone and tocilizumab was initiated at 9 days (6.5¿12), followed by HFNC at 9.5 days (7¿12). HFNC was maintained for an average of 4.5 days (2.8¿6.3), was successful in eighteen patients (90%), as defined by not needing invasive MV, and failed in two cases (10%) resulting in death. Since HFNC was implemented, there has been a decrease in the number of patients admitted to the ICU and treated with MV for acute hypoxic respiratory failure. Conclusions: HFNC administration may represent a viable therapeutic option for patients in the early stages of severe respiratory failure due to clinically suspected COVID-19. Keywords: oxygen; nasal cannula; respiratory insufficiency; hypoxia; COVID-19
Keywords: oxygen; nasal cannula; respiratory insufficiency; hypoxia; COVID-19